The dignity of the press - Johnson, George Victor (My University, 1891)
Introduction: The progressive spirit which characterizes our country is perhaps due more than anything else to the work of the printing press. Its influence has given the form to our civilization, and it is shaping the destiny of our people according to the character of its teachings and the principles in evolves. Especially in times when our country has been in a state of agitation, passing a period of transition, its powerful work has been realized by the way in which it has formed and given unity to public sentiment, given information of circumstances and kept the onward march toward the development of the customs of state into higher and better forms. The press has made diversity of knowledge possible. It has rendered immortal and free to all the great thoughts of master minds and valuable researches and discoveries of men of science. Its productions have assumed many uses and offices and with the development of its facilities of work its importance can hardly be realized. The American people could as well do without the most staple article of their food as they could do without the press and its products. The great amount of our regular and periodical literature shows the proportions its work has assumed. The press has been the stimulant which has caused the production of numerous books which are found so abundantly throughout our land and of which we feel so justly proud.
Citation: Johnson, George Victor. The dignity of the press. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Press; Newspaper; Media; Theses; Manuscripts (documents)